Contingency in/of the text: Aristotle, Hardy, Perec. Issue 3 (16th March 2018) - Ryle, Martin
ABSTRACT: Plots of realist novels often conform with Aristotle's view that literary works should exclude contingent events and relate what is 'probable or necessary'. Authors such as Eliot and Zola claim to produce social-historical knowledge based on the plot's mirroring of extra-textual causality. In such realism, chance events contribute (as in Hardy) to unitary meaning. Woolf is among the modernist inaugurators of a plot-free text that accommodates the 'disconnected and incoherent'. Georges Perec's Life a User ' s Manual pursues this aim via formal devices (Oulipian 'constraints') that supplant plot as a structural basis, creating a paradoxically underdetermined space in which contingency can appear.